TRANSLATION TECHNIQUES AND READABILITY OF THE CULTURE SPECIFIC ITEMS IN THE 2007 INDONESIAN TRANSLATION OF ALICE’S ADVENTURES IN WONDERLAND - Permatahati, Martinda Intan; Rosyidi, Mohamad Ikhwan (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
Translation techniques poses somewhat of challenge. Addressing the potential problems existing in translation between English and Indonesian, culture specific item (CSI) is used to translate the untranslatable words in the process of translation into target language. The technique that is used to translate will affect to the readability level. This research has an objective to find and describe the translation techniques that are applied in translating culture-specific items (CSI) in Sri Haryanto’s Indonesian translated novel of Alice’s Adventure in Wonderland entitled Petualangan di Negeri Ajaib dan Dunia di Balik Cermin by Windi A in 2007 and to explain the readability of culture-specific items (CSI) in this translated novel. Qualitative method is used in observing and analyzing the phenomenon which affected as an impact of the readability of culture-specific items in the translated text that had found in the Indonesian translated novel of Alice’s Adventures in Wonderland and also making interpretations of the meaning of the readability level of culture-specific items in its Indonesian translated novel through the readability rating-sheet. From this research, the researcher finds 16 translation techniques that are applied in translating the culture-specific items from Alice’s Adventure in Wonderland novel into its 2007 Indonesian translated novel by Sri Haryanto. Established equivalent translation technique is the highest frequency of translation technique that is applied in this novel. It can be concluded that the readability of culture-specific items in Sri Haryanto’s Indonesian translated novel of Alice’s in Wonderland is readable.